KEKERASAN DALAM RUMAH TANGGA: PENGARUHNYA TERHADAP PENDIDIKAN KARAKTER ANAK DAN SOLUSINYA PERSPEKTIF ISLAM - La Jamaa (IAIN Ambon, 2020)
The occurrence of domestic violence is considered had bad influence, either directly or indirectly to various acts of violence in the community, either fighting between the learner/student, motorcycle gang and between villages/areas as well as gangsterism in the community. It shows that domestic violence most affect the children's educational character. As the children learn and imitate and acquire knowledge of the use of violence at solving the problems. The children can learn and imitate from the violence acts committed by father to their mother, and peers, teachers/lecturers against him. To minimize the adverse effects of domestic violence, according to Islam is needed a solution through the children character education in three ways, namely: (1) choosing a husband/wife who has a good religiosity, (2) prevent children from the domestic violence atmosphere, especially when both parents are quarreled, and (3) provide the exemplary in doing good to the children from early age by combining the knowledge aspect of goodness, feel, and love the goodness and action (practice the goodness) so that children have good character, and did not wish doing violence to someone else.